THE POLITICAL CULTURE THAT AFFECTS THE STRENGTH OF THE BRASS PRODUCTION GROUP OF BAN PA AO, MUANG DISTRICT, AND THE GOAT FARMER’S COMMUNITY ENTERPRISE GROUP, BAN BUA THA, SAWANG WEERAWONG DISTRICT, UBON RATCHATHANI PROVINCE - Moolsin, Worabhuri (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
This research article the objectives are 1. To study the political culture that affects Strength of the Ban Pa-ao Brass Production Group and Ban Bua Tha Goat Farming Community Enterprise Group in Ubon Ratchathani Province 2. To study the problems and obstacles affecting the strengthening process 3. To study the method for building success of the production group Ban Pa-Ao Brass and Goat Farmers’s Community Enterprise Group in Ubon Ratchathani Province. Quality research is used, the researcher collected both primary data and secondary data. Members of the Ban Pa-ao Brass Production Group from Mueang District, Ubon Ratchathani Province, served as the sample group for the study. Along with the Goat Raising Community Enterprise Group in Sawang Wirawong District’s Ban Bua Tha. Ratchathani Province of Ubon The study included interviews and content analysis for data analysis. The results showed that 1. the savings group made brass at Baan Pa-Ao. and the Goat Farmer’s Community Enterprise Group, Ban Bua Tha, the group committee Most commented that the group’s political culture was participant political culture, and everyone could express their opinions. For members of the group, there is a cultural society of the group as a traditional rural way of life with kinship ties. 2. The problems and obstacles to the strengthening process are due to the decrease in the number of artisans due to the production time, and finding a cost-effective way manufacturing brassware in less time. While working as a day laborer elsewhere earning more than making brass. The Goat farmers group has encountered the same problem; most of the members resigned, because they were unwilling to raise goats. To be employed as a construction contractor in the city. 3. The guidelines for success of the group are that If supported by government agencies Department of Community Development, District Agriculture with incentives to pass on knowledge of new operations, find cheaper sources of funds to buy brass or to buy goats, including the management will make it a much more effective management.